1980
DOI: 10.1002/1097-0142(19800815)46:4+<919::aid-cncr2820461311>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of pre-invasive breast carcinoma

Abstract: Improvements in mammography in the past 25 years have made it possible to detect before surgery many lesions with a high probability of being pre-invasive carcinoma. Because these cancers are virtually all cured by mastectomy, there has been considerable interest in alternative types of treatment. Retrospective studies of pre-invasive carcinoma treated by biopsy only revealed subsequent carcinoma in 30 to 40% of patients. Among women with lobular carcinoma in situ (LCIS), the frequency of subsequent carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
113
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(119 citation statements)
references
References 17 publications
(1 reference statement)
5
113
0
1
Order By: Relevance
“…However, such studies have been rare, and the most recent of these were published more than a decade ago. [17][18][19][20][21] Furthermore, in two of the three previous studies of this type, [17][18][19][20] the DCIS lesions were classified primarily by architectural growth pattern rather than nuclear grade, because that was the standard manner in which DCIS was classified at the time those studies were conducted. Given the recent trend toward classifying DCIS based primarily on nuclear grade, 22,23 it is somewhat difficult to extrapolate the results of these earlier studies to DCIS cases as currently classified.…”
Section: Conclusion These Results Provided Further Evidence That Pamentioning
confidence: 99%
See 2 more Smart Citations
“…However, such studies have been rare, and the most recent of these were published more than a decade ago. [17][18][19][20][21] Furthermore, in two of the three previous studies of this type, [17][18][19][20] the DCIS lesions were classified primarily by architectural growth pattern rather than nuclear grade, because that was the standard manner in which DCIS was classified at the time those studies were conducted. Given the recent trend toward classifying DCIS based primarily on nuclear grade, 22,23 it is somewhat difficult to extrapolate the results of these earlier studies to DCIS cases as currently classified.…”
Section: Conclusion These Results Provided Further Evidence That Pamentioning
confidence: 99%
“…[17][18][19][20][21] The study of Betsill et al, 17 updated by Rosen et al, 18 reported 30 patients with low-grade papillary intraductal carcinoma treated with biopsy alone. Two of these patients also had lobular carcinoma situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As documented by Page et al and others in their long-term follow-up evaluations of the natural history of DCIS treated by biopsy only, reaffirming low-grade DCIS as a nonobligate precursor to invasive cancer, we would expect columnar cell atypia to evolve, as a precursor, into the lesion it presumably precedes. [29][30][31][32][33] In other words, the most persuasive argument for progression remains documentation of actual progression rather than mere co-occurrence. So far, the available studies have failed to substantiate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the local recurrences after treatment for a primary DCIS are invasive (Rosen et al, 1980;Page et al, 1982;Bradley et al, 1990;Price et al, 1990;Graham et al, 1991;Swain, 1992;Fisher et al, 1993;Solin et al, 1996). Autopsy studies, however, strongly suggest that not all DCIS lesions progress to invasiveness during a patient's lifetime (Andersen et al, 1985).…”
mentioning
confidence: 99%